REGULATING CREATIVITY: THE EVOLUTION, MECHANISMS, AND IMPACT OF CHINA’S FILM CENSORSHIP SYSTEM - Zheng Jiaqi; Wan Aida Wan Yahaya; Sanghamitra Dalal, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
China’s film censorship system, deeply rooted in state control and ideological oversight, has evolved from decentralized regulation in the Republican era to a highly institutionalized framework under the People’s Republic. This study examines its key mechanisms—pre-production approvals, content restrictions, post-production editing, and self-censorship—highlighting their impact on creative expression and industry growth.Amid calls for reform, debates persist over adopting a film rating system as a viable alternative. Comparing international models, this paper explores the contradictions between China’s industrial modernization and rigid censorship, underscoring tensions between traditional values and contemporary market demands.While full liberalization remains improbable, a dual-track system integrating censorship and classification may offer a pragmatic path forward. As China’s film industry globalizes, balancing state interests with artistic freedom and audience autonomy will be critical in shaping the future of its regulatory framework.